Particulate Matter 2.5 Induced Developmental Cardiotoxicity in Chicken Embryo and Hatchling - Jiang, Qixiao; Zhang, Chao; Chen, Shen; Shi, Limei; Li, Dao Chuan; Lv, Na; Cui, Lianhua; Chen, Yanxia; Zheng, Yuxin (Frontiers in Pharmacology, 2020)
Particulate matter poses health risk to developing organisms. To investigate PM2.5-induced developmental cardiotoxicity, fertile chicken eggs were exposed to PM2.5 via air cell injection at doses of 0.05, 0.2, 0.5, 2 and 5 mg/egg kg. Morphological changes in the ED4 and hatchling hearts were assessed with histological techniques. Heart rates of hatchling chickens were measured with electrocardiography. The protein expression levels of NF-kb p65, iNOS and MMP9 were assessed with immunohistochemistry or western blotting in hatchling hearts. PM2.5 exposure elevated areas of heart in ED4 embryo, increased heart rate and thickened right ventricular wall thickness in hatchling chickens. Immunohistochemistry revealed enhanced NF-kb p65 expression in hatchling hearts. Western blotting results indicated that both iNOS and MMP9 expression were enhanced by lower doses of PM2.5 exposure (0.2 and 0.5 mg/kg) but not 2 mg/kg. In summary, developmental exposure to PM2.5 induced developmental cardiotoxicity in chicken embryo and hatchling chickens, which is associated with NF-kb p65, iNOS and MMP9.